Strategi Dan Pendekatan Pendidikan Islam Di Era Modernisasi Menurut Perspektif Mastuhu - Sholihuddin, Muhammad; Alifiyah, Rizka; Zaenab, Siti; Faizin, M. (Program Studi Pendidikan Agama Islam, 2024)
Education is very important need for developing the quality of human resources. With quality education, it can improve the welfare and standard of living of an individual and also the surrounding community. A strategy is needed in an effort to improve the quality of education in the current era of modernization. Especially in Islamic education as a national education system that aspires to form a muslim with integrity, ethics and noble character. The research uses qualitative research methods through literature analysis, case studies, and related sources. By analyzing information about strategies and education according to the perspective of an Islamic education expert, amastuhu. So that information is produced about the strategy of Islamic education in the era of modernization in the form of descriptive narratives.